PERAN DAN TANGGUNG JAWAB ORANG TUA MENDIDIK ANAK SECARA ISLAMI DALAM RUMAH TANGGA - Halid Hanafi (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2024)
Parents are the first teachers for children in the order of family life. Parents have a big role and responsibility in efforts to instill Islamic education for children in the family environment so that children can grow physically and spiritually in life in accordance with the values ??of Islamic teachings. This research uses a library method by conducting an in-depth and systematic study of various relevant literature sources so that appropriate answers are obtained regarding the problems studied. Islamic education is all forms of educational activities to direct humanity to live in accordance with the values ??of Islamic teachings. The role and responsibility of parents to educate their children Islamically is to strive to develop the child both physically and spiritually from the time he is born until he reaches maturity with the values ??of Islamic teachings so that the child lives in accordance with the values ??of Islamic teachings. For this reason, parents have a role in cultivating children's personalities so that they can live a life in accordance with the values ??of Islamic teachings, where if the values ??of Islamic teachings are well instilled in children, the children will grow up with Islamic personalities in their lives.